Mapeamento da produtividade e perímetro do tronco de clones de seringueira em argissolo vermelho amarelo - Roque, Cassiano Garcia [UNESP]; Centurion, José Frederico [UNESP]; Pereira, Gener Tadeu [UNESP]; Beutler, Amauri Nelson [UNESP]; Da Silva Freddi, Onã [UNESP]; Andrioli, Itamar [UNESP] (My University, 2006)
This work had the objective to evaluate the dry rubber yield (BS), to correlate this with the girth (PT), as well as evaluating the spatial variability of these in a Kandiustalf, cultivated with the rubber clones PB 235 and RRIM 600. For the evaluation of spatial variability it was mounted a grid totalizing 180 points, for each clone. The BS was evaluated using the tapping system 1/2S d/5 6d/7 10m/y ET 2,5% Pa 6/y. The trunk girth (PT) was evaluated at 1.30 m height from the ground. The averages of BS were compared through test t student and analysis of regression between the BS and the PT. The results were submitted to procedures of descriptive statistics and the spatial dependence was verified by means of semivariograms. The BS of clone PB 235 was greater that of clone RRIM 600. The PT influenced in the BS. The spatial variability of the BS was related with the PT.
Mapping of the yield and girth of rubber tree clones in kandiustalf
Keywords: Geoestatistic; Hevea brasiliensis; Kriging; Forestry; Regression analysis; Rubber; Hevea; Regression Analysis